Scientific Validation of Human Neurosphere Assays for Developmental Neurotoxicity Evaluation - Koch, Katharina; Bartmann, Kristina; Hartmann, Julia; Kapr, Julia; Klose, Jördis; Kuchovská, Eliška; Pahl, Melanie; Schlüppmann, Kevin; Zühr, Etta; Fritsche, Ellen (Frontiers in Toxicology, 2022)
There is a call for a paradigm shift in developmental neurotoxicity (DNT) evaluation, which demands the implementation of faster, more cost-efficient, and human-relevant test systems than current in vivo guideline studies. Under the umbrella of the Organisation for Economic Co-operation and Development (OECD), a guidance document is currently being prepared that instructs on the regulatory use of a DNT in vitro battery (DNT IVB) for fit-for-purpose applications. One crucial issue for OECD application of methods is validation, which for new approach methods (NAMs) requires novel approaches. Here, mechanistic information previously identified in vivo, as well as reported neurodevelopmental adversities in response to disturbances on the cellular and tissue level, are of central importance. In this study, we scientifically validate the Neurosphere Assay, which is based on human primary neural progenitor cells (hNPCs) and an integral part of the DNT IVB. It assesses neurodevelopmental key events (KEs) like NPC proliferation (NPC1ab), radial glia cell migration (NPC2a), neuronal differentiation (NPC3), neurite outgrowth (NPC4), oligodendrocyte differentiation (NPC5), and thyroid hormone-dependent oligodendrocyte maturation (NPC6). In addition, we extend our work from the hNPCs to human induced pluripotent stem cell-derived NPCs (hiNPCs) for the NPC proliferation (iNPC1ab) and radial glia assays (iNPC2a). The validation process we report for the endpoints studied with the Neurosphere Assays is based on (i) describing the relevance of the respective endpoints for brain development, (ii) the confirmation of the cell type-specific morphologies observed in vitro, (iii) expressions of cell type-specific markers consistent with those morphologies, (iv) appropriate anticipated responses to physiological pertinent signaling stimuli and (v) alterations in specific in vitro endpoints upon challenges with confirmed DNT compounds. With these strong mechanistic underpinnings, we posit that the Neurosphere Assay as an integral part of the DNT in vitro screening battery is well poised for DNT evaluation for regulatory purposes.